Listener response as a facet of interactional competence. (July 2018) - Ross, Steven
Interactional competence has been variously defined as turn-taking ability, paralinguistic features of communication such as eye contact, gesture, and gesticulation, and listener responses. In existing assessment systems such as the oral proficiency interview (OPI), interactional competence is only rarely explicitly factored into the holistic task-based rating system. The present article explores the potential relevance of a facet of interactional competence, listener response, in contrastive interviewers conducted structurally distinct languages, Japanese and English. The analytic focus through micro-analysis of the interview interaction aims to consider evidence of how the candidate's listener responses audible through backchannels might be consistently identified as distinct from existing rating criteria such as fluency, accuracy, and coherence, and whether listener responses as interactional competence might be distinct from, or subsumable under, these facets of speaker proficiency.